High-diffusion-coefficient sodium ion battery negative electrode material as well as preparation method and application thereof
By introducing oxygen defects into the negative electrode material of KTiOPO4 of sodium ion battery and optimizing the crystal structure, the problem of its low diffusion coefficient is solved, and the performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202510131885.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-05-06
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The diffusion coefficient of the sodium ion battery negative electrode material KTiOPO4 is low, limiting the battery charge and discharge rate and cycle life.
The oxygen defects with specific content are prepared by later hydrogen annealing, and the crystal structure of the material is optimized by using staged sintering and atmosphere control methods to improve the diffusion coefficient of sodium ions.
It significantly improves the diffusion coefficient of sodium ions, improves the charge and discharge rate and cycle life of the battery, and maintains the structural stability of the material.
Smart Images

Figure CN119929770A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high diffusion coefficient sodium ion battery negative electrode material and a preparation method and application thereof, belonging to the technical field of batteries. Background Art
[0002] In today's energy storage field, sodium-ion batteries have attracted much attention due to their abundant sodium resources and relatively low cost. However, the performance of sodium-ion batteries still needs to be improved, especially in terms of negative electrode materials.
[0003] Among the titanium-based phosphates used as negative electrode materials for sodium-ion batteries, KTiOPO4 (KTOP) has a larger cross-cavity and the lowest potential of KTiOPO4, which is 1.23V. It has great potential in achieving faster ion dynamics and lower cycle strain in sodium-ion batteries. However, the diffusion coefficient of this material is low, which severely limits the charge and discharge rate and cycle life of the battery. Traditional material preparation methods can regulate the electronic structure through doping engineering, intercalation engineering and other methods, which can change the valence state of metal ions, atomic coordination environment, charge density distribution and energy band structure, thereby optimizing electrochemical performance and improving ionic conductivity. However, these measures are not effective for KTOP materials. How to introduce defects into KTOP through a simple and effective preparation method to increase the ion diffusion rate is a topic worth studying. Summary of the invention
[0004] In order to solve the above problems, the present invention prepares a specific content of oxygen defects through post-hydrogen annealing without adversely affecting the crystal structure of the material, thereby obtaining a high diffusion coefficient sodium ion battery negative electrode material.
[0005] The first object of the present invention is to provide a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps:
[0006] S1. Press K 1-2x TiO 1-x The phosphorus source, potassium source, and titanium source are mixed in a stoichiometric ratio of PO4, and then mixed with a carbon source to obtain a slurry; wherein x = 0.001-0.1;
[0007] S2, drying the slurry of S1 to obtain a precursor;
[0008] S3, the precursor of S2 is treated in three stages to obtain a chemical formula of K 1-2x TiO 1-x PO4@C is a negative electrode material for sodium-ion batteries;
[0009] The three-stage process includes:
[0010] The first stage: heating to a first set temperature for heat treatment in an inert gas atmosphere;
[0011] The second stage: the product of the first stage is cooled to 400-600°C in a hydrogen atmosphere for heat treatment;
[0012] The third stage: the product of the second stage is cooled to the second set temperature at a rate of 10-20°C / min under a hydrogen atmosphere.
[0013] In the prior art, the negative electrode material of sodium ion batteries, potassium titanyl phosphate (KTOP), has many problems such as low diffusion coefficient, poor conductivity, complex preparation process and high cost. This is related to the fact that the ion channels inside the KTOP crystal are restricted by the crystal structure, resulting in poor ion transmission. The ion channel is a path in the crystal structure that allows ions to pass through. The KTOP crystal has a complex three-dimensional framework structure, which contains many tiny channels and gaps. If these channels are not smooth, the diffusion path of ions inside the crystal will become complicated, and the transmission speed of ions will be significantly reduced. Therefore, how to improve the diffusion coefficient of the material by optimizing the crystal structure and ion channels to improve battery performance is the main research focus of the present invention.
[0014] In the process of preparing crystalline materials, high-temperature hydrogen annealing is used to "artificially" create oxygen defects, thereby achieving the purpose of improving the electrical conductivity of the material. Therefore, the present invention proposes a new method for preparing a negative electrode material for a sodium ion battery with a high diffusion coefficient. The present invention sintered the carbon-coated KTOP precursor in stages. The first stage is mainly related to the structural formation of KTOP. The second stage is kept warm at 400-600°C and the protective atmosphere is changed to hydrogen. Combined with the rapid cooling method in the third stage, a certain amount of oxygen defects can be formed and the oxygen defects can be "fixed". This unique sintering method and atmosphere control greatly optimize the crystal structure of the material, thereby significantly improving the diffusion coefficient of sodium ions in the material. In particular, although there are many ways to form oxygen defects, after research we found that different introduction methods have different effects on the KTOP lattice structure. The formation of some oxygen defects will cause the lattice to expand or contract, which has an adverse effect on the material capacity: for example, oxygen defects introduced by doping metal or non-metal ions will also introduce additional defect energy levels, affecting the electronic structure and electrical properties of the material; for example, oxygen defects introduced by chemical reaction methods will form new active sites on the surface of the material, which may cause some undesirable electrochemical reactions to occur, affecting the stability of the material surface. Therefore, these methods were abandoned in the preliminary experiment. Only when hydrogen annealing is supplemented with certain cooling conditions, oxygen defects not only increase the ion migration sites in the material, but also the oxygen defects formed by the present invention can play a role in adjusting the electronic structure of the material and reducing the charge transfer resistance, significantly improving the diffusion coefficient of ions, and the specific capacity of the material increases instead of decreasing, and the diffusion coefficient is improved by at least one order of magnitude, which has the greatest improvement in battery performance.
[0015] Preferably, the heat treatment temperature in the second stage is 400-600°C, such as 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 595°C, 599°C, etc., including but not limited to the values listed above. More preferably, it is 500°C.
[0016] Preferably, the cooling rate in the third stage is 10-20°C / min, such as 10.5°C / min, 11°C / min, 11.5°C / min, 12°C / min, 13°C / min, 14°C / min, 14.5°C / min, 15.5°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 19.5°C / min, etc., including but not limited to the values listed above. More preferably, it is 15°C / min.
[0017] Furthermore, in step S1, at least one of the following is included:
[0018] (1) The potassium source includes one or more of potassium carbonate, potassium hydroxide, potassium sulfate and potassium dihydrogen phosphate, preferably potassium dihydrogen phosphate;
[0019] (2) The titanium source includes one or more of titanium dioxide, metatitanic acid, titanic acid and titanium tetrachloride, preferably titanium dioxide;
[0020] (3) The phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate and phosphorus pentoxide;
[0021] (4) The carbon source includes one or more of graphite, activated carbon, hard carbon, graphene and carbon black.
[0022] Furthermore, in step S1, at least one of the following is included:
[0023] (1) In the sodium ion battery negative electrode material, the mass percentage of the carbon source is 1-5wt%;
[0024] (2) The mixing method includes wet ball milling;
[0025] (3) The mixing comprises the following steps: firstly mixing a phosphorus source, a potassium source and a titanium source to obtain slurry A, and then mixing slurry A with a carbon source to obtain slurry B;
[0026] (4) The slurry contains a solvent; the solvent includes water or a mixed solvent of water and ethanol (the content of ethanol in the mixed solvent is 0.1-10wt%).
[0027] Preferably, the mass percentage of the carbon source is 1-5wt%, such as 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 4.8wt%, 4.9wt%, etc., including but not limited to the values listed above. More preferably, it is 2wt%.
[0028] Further, in step S2, the drying comprises at least one of the following:
[0029] The drying method includes centrifugal spray drying;
[0030] Preferably, the inlet air temperature of the centrifugal spray drying is 100-240°C;
[0031] Preferably, the outlet air temperature of the centrifugal spray drying is 80-110°C;
[0032] Preferably, the centrifugal speed of the centrifugal spray drying is 10000-20000 rpm.
[0033] Furthermore, in the first stage of step S3, at least one of the following is included:
[0034] (1) The inert gas includes argon and / or hydrogen;
[0035] (2) The first set temperature is 600-800° C.;
[0036] (3) The heating rate is 1-10°C / min;
[0037] (4) The heat treatment time is 10-20 hours;
[0038] (5) The flow rate of the inert gas is 5-15 L / min.
[0039] Preferably, the first set temperature is 600-800°C, such as 610°C, 630°C, 650°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 795°C, etc., including but not limited to the values listed above. More preferably, it is 700°C.
[0040] Preferably, the heating rate is 1-10°C / min, such as 1.5°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 9.5°C / min, etc., including but not limited to the values listed above. More preferably, it is 3°C / min.
[0041] Preferably, the heat treatment time is 10-20 hours, such as 10.5 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 19.5 hours, etc., including but not limited to the values listed above, and more preferably 12 hours.
[0042] Preferably, the flow rate of the inert gas is 5-15 L / min, such as 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 14.5 L / min, etc., including but not limited to the values listed above. More preferably, it is 8 L / min.
[0043] Furthermore, in the second stage of step S3, at least one of the following is included:
[0044] (1) The heat treatment time is 2-10 hours;
[0045] (2) The cooling rate is 1-10°C / min;
[0046] (3) The flow rate of the hydrogen is 10-20 L / min.
[0047] Preferably, the heat treatment time is 2-10 hours, such as 2.5 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 9.5 hours, etc., including but not limited to the values listed above, and more preferably 5 hours.
[0048] Preferably, the cooling rate is 1-10°C / min, such as 1.5°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 9.5°C / min, etc., including but not limited to the values listed above. More preferably, it is 5°C / min.
[0049] Preferably, the flow rate of hydrogen is 10-20 L / min, such as 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, 16 L / min, 17 L / min, 18 L / min, 19 L / min, etc., including but not limited to the values listed above, and more preferably 12 L / min.
[0050] Furthermore, at least one of the following is included:
[0051] (1) When the heat treatment time is 2 h, the flow rate of hydrogen is greater than 10 L / min;
[0052] (2) When the flow rate of the hydrogen is 10 L / min, the heat treatment time is greater than 2 h;
[0053] (3) When the heat treatment time is 10 h, the flow rate of hydrogen is less than or equal to 20 L / min;
[0054] (4) When the flow rate of the hydrogen is 20 L / min, the heat treatment time is less than or equal to 10 h.
[0055] Furthermore, in the third stage of step S3, at least one of the following is included:
[0056] (1) The second set temperature is 20-30°C (room temperature);
[0057] (2) The flow rate of the hydrogen is 10-20 L / min;
[0058] (3) The cooling method includes liquid cooling or air cooling.
[0059] Preferably, the flow rate of hydrogen is 10-20 L / min, such as 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, 16 L / min, 17 L / min, 18 L / min, 19 L / min, etc., including but not limited to the values listed above, and more preferably 15 L / min.
[0060] The present invention configures slurry A according to the stoichiometric ratio, and then adds a specific content of carbon source for wet ball milling to obtain slurry B. Here, the carbon source has a wide range of choices and the content is precisely controlled at 1-5wt%, which effectively improves the conductivity and structural stability of the material. Then, the slurry is made into a spherical precursor mixed powder by a centrifugal spray drying method, and the inlet temperature, outlet temperature and centrifugal rate are controlled to make the precursor have a good morphology and particle size distribution. Then, through a staged sintering process, as well as changes in the atmosphere, especially hydrogen annealing to produce oxygen defects, a sodium ion battery negative electrode material with a high diffusion coefficient is prepared.
[0061] The second object of the present invention is to provide a sodium ion battery negative electrode material prepared by the above preparation method, wherein the chemical formula of the sodium ion battery negative electrode material is K 1-2x TiO 1-x PO4@C, where x = 0.001-0.1, produces a certain amount of oxygen defects through hydrogen annealing.
[0062] Preferably, x=0.001-0.1, such as 0.002, 0.005, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, 0.05, 0.07, 0.09, 0.1, etc., including but not limited to the values listed above. More preferably, it is 0.01-0.02.
[0063] The third object of the present invention is to provide a negative electrode plate, which comprises a current collector and a negative electrode active layer arranged on at least one side of the current collector along the thickness direction, and the negative electrode active layer contains the sodium ion battery negative electrode material.
[0064] Furthermore, the negative electrode active layer comprises the following components in mass percentage: 75-95% of negative electrode material, 5-15% of conductive agent and 5-15% of binder.
[0065] Furthermore, the current collector is aluminum foil, or other materials that can be used as current collectors.
[0066] Furthermore, the conductive agent used in the present invention is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
[0067] Further, the binder can be a binder well known to those skilled in the art without special restrictions, such as chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer. In the embodiment of the present invention, PVDF (polyvinylidene fluoride) is selected.
[0068] A fourth object of the present invention is to provide a sodium ion battery comprising the negative electrode plate.
[0069] Furthermore, the sodium ion battery also contains an electrolyte, and the electrolyte contains a sodium salt electrolyte.
[0070] Furthermore, the electrolyte can be any electrolyte well known to those skilled in the art without any special restrictions, the solvent is at least one of ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate and diethylene glycol dimethanol ether; the electrolyte salt is at least one of sodium perchlorate, sodium bis(oxalate)borate, and sodium hexafluorophosphate.
[0071] Beneficial effects of the present invention:
[0072] Due to the advanced nature of this technical solution, it can be widely used in the fields of sodium ion battery material preparation technology, material surface treatment technology and hydrogen annealing technology:
[0073] First, in the field of sodium ion battery material preparation technology, the present invention provides a method for improving the diffusion coefficient of powder materials by manufacturing oxygen defects and metal ion defects by means of late hydrogen annealing. This method can effectively solve the problem of low diffusion coefficient when KTiOPO4 is used as a negative electrode material for sodium ion batteries, thereby improving the performance of sodium ion batteries. With the widespread application of sodium ion batteries, the demand for high-performance positive and negative electrode materials is increasing. The present invention provides an effective solution and has broad market prospects.
[0074] Secondly, in the field of material surface treatment technology, the present invention treats KTiOPO4 by hydrogen annealing in the later stage, which can improve the diffusion coefficient of the material and thus improve its performance. This method can be extended to other material surface treatment fields, such as lithium-ion battery materials, supercapacitor materials, etc., to improve the dispersibility and conductivity of these materials and improve their performance.
[0075] In general, the present invention has significant technical advantages and broad application prospects in improving the performance of sodium ion batteries, improving the surface properties of materials and optimizing the hydrogen annealing process. With the continuous advancement of technology and the growth of market demand, the present invention is expected to play an important role in related fields and promote the development and application of related technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is the charge and discharge curve of the material prepared in Example 1. DETAILED DESCRIPTION
[0077] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0078] The preparation method involved in the present invention is as follows:
[0079] 1) Slurry A is prepared with a phosphorus source, a potassium source and a titanium source in a stoichiometric ratio; then a carbon source is added and slurry B is prepared by wet ball milling; the carbon source is one or more of graphite, activated carbon, hard carbon, graphene and carbon black; and the content of the carbon source is 1-5wt%.
[0080] 2) The slurry B is subjected to a centrifugal spray drying method to obtain a spherical carbon-coated potassium titanyl phosphate compound precursor mixed powder;
[0081] 3) Sintering the precursor mixed powder to obtain carbon-coated potassium titanyl phosphate compound powder; the sintering is carried out in three stages: the first stage is sintering at a constant temperature of 600-800°C for 10-20 hours under a protective atmosphere, and the protective atmosphere is an inert gas such as nitrogen and argon; the second stage is after the first stage, the insulation temperature is 400-600°C, the insulation time is 2-10 hours, and the protective atmosphere is hydrogen. The third stage is a cooling stage, which is cooled to room temperature at a certain cooling rate, and the cooling method is liquid cooling or air cooling.
[0082] Preferably, the air inlet temperature of the centrifugal spray drying is 100-240°C, the air outlet temperature is controlled at 80-110°C, and the centrifugal speed is set at 10000-20000 rpm. More preferably, the air inlet temperature can be controlled at 200-240°C, the air outlet temperature is controlled at 100-110°C, and the centrifugal speed is set at 12000-15000 rpm to obtain a spherical carbon-coated potassium titanyl phosphate compound precursor mixed powder.
[0083] Preferably, in the first stage, the temperature is raised to 600-800° C. at a heating rate of 1-10° C. / min, and the gas flow rate is 5-15 L / min.
[0084] Preferably, in the second stage, the temperature is reduced to 400-600° C. at a rate of 1-10° C. / min, and the gas flow rate is 10-20 L / min.
[0085] Preferably, in the third stage, the temperature is lowered to 20-30°C at a cooling rate of 10-20°C / min, and the gas flow rate is 10-20 L / min.
[0086] Example 1
[0087] 1) Prepare slurry A with a phosphorus source, a potassium source and a titanium source in a stoichiometric ratio of 1:1:1; then add a carbon source and wet-mill to obtain slurry B; the solvent for wet-milling is water. Specifically, KH2PO4 is used as a K source and a P source, TiO2 is used as a Ti source, deionized water is added and mixed evenly, and then 2wt% acetylene black is added as a carbon source, with a solid content of 50%, and a vertical ball mill is used for 4h to mix evenly.
[0088] 2) Slurry B is subjected to centrifugal spray drying to obtain spherical carbon-coated potassium titanyl phosphate compound precursor mixed powder; the inlet air temperature is controlled at 220° C., the outlet air temperature is controlled at 110° C., and the centrifugal speed is set at 13,000 rpm.
[0089] 3) Sintering the precursor mixed powder, the sintering is carried out in three stages:
[0090] First, the temperature was raised to 750 °C at a rate of 3 °C / min under nitrogen atmosphere and kept at this temperature for 12 h, with a gas flow rate of 8 L / min;
[0091] Then the protective atmosphere was changed to hydrogen with a gas flow rate of 12 L / min, and the temperature was decreased to 500 °C at a rate of 5 °C / min, and the holding time was 5 h;
[0092] Finally, the mixture was cooled to room temperature by air at a rate of 15°C / min, and the protective atmosphere was still hydrogen. Finally, carbon-coated potassium titanyl phosphate compound powder was obtained.
[0093] Example 2
[0094] The second stage insulation temperature in step 3) is adjusted from 500°C to 400°C, and the rest is the same as in Example 1.
[0095] Example 3
[0096] The second stage insulation temperature in step 3) is adjusted from 500°C to 600°C, and the rest is the same as in Example 1.
[0097] Example 4
[0098] The cooling rate of the third stage in step 3) was adjusted from 15°C / min to 10°C / min, and the rest was the same as in Example 1.
[0099] Example 5
[0100] The cooling rate of the third stage in step 3) was adjusted from 15°C / min to 20°C / min, and the rest was the same as in Example 1.
[0101] Example 6
[0102] (1) The gas flow rate of the second stage in step 3) was adjusted from 12 L / min to 10 L / min, and the insulation time was adjusted from 5 hours to 10 hours. The rest was the same as in Example 1.
[0103] (2) The gas flow rate of the second stage in step 3) was adjusted from 12 L / min to 20 L / min, and the insulation time was adjusted from 5 hours to 2 hours. The rest was the same as in Example 1.
[0104] (3) The gas flow rate of the second stage in step 3) was adjusted from 12 L / min to 10 L / min, and the insulation time was adjusted from 5 hours to 2 hours. The rest was the same as in Example 1.
[0105] Example 7
[0106] (1) The insulation temperature of the first stage in step 3) was adjusted from 750°C to 600°C, and the insulation time was adjusted from 12 h to 10 h. The rest was the same as in Example 1.
[0107] (2) The insulation temperature of the first stage in step 3) was adjusted from 750° C. to 800° C., and the insulation time was adjusted from 12 h to 20 h. The rest was the same as in Example 1.
[0108] (3) The heating rate of the first stage in step 3) was adjusted from 3°C / min to 10°C / min, and the gas flow rate was adjusted from 8 L / min to 15 L / min, and the rest was the same as in Example 1.
[0109] (4) The heating rate of the first stage in step 3) was adjusted from 3°C / min to 1°C / min, and the gas flow rate was adjusted from 8 L / min to 5 L / min. The rest was the same as in Example 1.
[0110] Example 8
[0111] (1) The cooling rate of the second stage in step 3) was adjusted from 5°C / min to 10°C / min, and the gas flow rate was adjusted from 8L / min to 10L / min, and the rest was the same as in Example 1.
[0112] (2) The cooling rate of the second stage in step 3) was adjusted from 5°C / min to 1°C / min, and the gas flow rate was adjusted from 8L / min to 20L / min, and the rest was the same as in Example 1.
[0113] Comparative Example 1
[0114] The second stage insulation temperature in step 3) is adjusted from 500°C to 300°C, and the rest is the same as in Example 1.
[0115] Comparative Example 2
[0116] The second stage insulation temperature in step 3) is adjusted from 500°C to 800°C, and the rest is the same as in Example 1.
[0117] Comparative Example 3
[0118] The cooling rate of the third stage in step 3) was adjusted from 15°C / min to 5°C / min, and the rest was the same as in Example 1.
[0119] Comparative Example 4
[0120] Replace step 3) with the following steps, and the rest is the same as in Example 1:
[0121] The precursor mixed powder was heated to 750° C. at a rate of 3° C. / min in a nitrogen atmosphere and kept warm for 12 hours with a gas flow rate of 8 L / min to obtain a carbon-coated potassium titanyl phosphate compound powder.
[0122] Comparative Example 5
[0123] In general, oxygen defects can be formed by hydrogen annealing or high-temperature sintering. When preparing electrode materials by high-temperature sintering, due to the high temperature, oxygen atoms obtain enough energy to break free from the lattice constraints and escape from the material surface, leaving vacancies in the lattice to form oxygen defects. As mentioned in the previous research on materials, oxygen loss occurs in both the bulk and surface of the sample after high-temperature sintering, forming oxygen defects.
[0124] Therefore, we studied whether high temperature sintering is suitable for forming an ideal KTOP material with oxygen defects: step 3) was replaced by the following steps, and the rest was the same as in Example 1:
[0125] The precursor mixed powder was heated to 950° C. at a rate of 3° C. / min in a nitrogen atmosphere and kept warm for 12 h with a gas flow rate of 8 L / min to obtain a carbon-coated potassium titanyl phosphate compound powder.
[0126] Test Case
[0127] Sodium ion batteries were constructed using the negative electrode materials prepared in the above embodiments and comparative examples, and the electrical properties of each battery were tested.
[0128] Chemical formula determination: The prepared material is heated in air at 500-600°C to remove the coated carbon, and then the chemical formula of the material is determined by ICP testing the content of each element.
[0129] Specific capacity test: The obtained negative electrode material, superP, and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and NMP was added and stirred to obtain an active slurry. The positive electrode active slurry was evenly coated on the surface of the aluminum foil current collector, and a 200um blade coating was performed to prepare a pole piece. The pole piece was obtained after drying and cold pressing. The mass loading of the active material was about 2.5 mg cm -2 . The counter electrode is a metal sodium sheet. PE is selected as the separator with a thickness of 10μm. Cell assembly: Arrange the positive electrode sheet, separator, negative electrode sheet, and separator in sequence, and use winding as the assembly method. Preparation of electrolyte: Sodium hexafluorophosphate is dissolved in ethylene carbonate with a concentration of 1mol / L. The button cell assembled above is subjected to conventional 0.1C charge and discharge characterization, and the charge and discharge voltage range is 0-3V.
[0130] Sodium ion diffusion coefficient test: the ion diffusion coefficient of the material is tested by the constant current intermittent titration method (GITT).
[0131] The results are as follows:
[0132] Table 1 Test results
[0133]
[0134] From the comparison between Example 1-3 and Comparative Example 1-2, we can see the effect of hydrogen annealing temperature on the product: when the annealing temperature is between 400-600°C, the content of oxygen defects in the material is about 1%. As the temperature rises, the oxygen defect content and specific capacity increase slightly, and the diffusion coefficient is in the order of 10 to the -9th power. When the annealing temperature is less than 400°C, due to the low annealing temperature, the ability of hydrogen to capture oxygen atoms is insufficient and oxygen defects cannot be formed. At this time, the specific capacity decreases by about 20%, and the diffusion coefficient also decreases to the order of 10 to the -10th power; when the temperature is higher than 600°C, there are too many oxygen defects, causing lattice collapse, resulting in a sharp drop in the specific capacity and diffusion coefficient of the material.
[0135] From the comparison between Examples 4-5 and Comparative Example 3, we can see the effect of the cooling rate in the third stage on the product: as the cooling rate increases, the oxygen defects generated in the second stage can be well maintained. When the cooling rate drops below 10°C / min, the oxygen defects generated in the second stage will be compensated by cation segregation during the cooling process and cannot be well retained. We speculate that if the cooling rate is increased to more than 20°C / min, more oxygen defects may be formed, but since powder sintering generally uses a push plate kiln or a roller kiln, it is difficult to achieve such a fast cooling rate.
[0136] It can be seen from Example 6 that when the holding temperature of the second stage and the cooling rate of the third stage are determined, the gas flow rate and the holding time of the second stage affect each other. When the gas flow rate is relatively small, the holding time needs to be appropriately extended, and vice versa. However, when the flow rate and time are both at the lower limit, the effect of hydrogen reduction to obtain oxygen defects is basically not achieved.
[0137] It can be seen from Example 7 that the sintering temperature, duration, heating rate and gas flow rate of the first stage have no obvious effect on the oxygen defect formation effect of the product, and a certain oxygen defect can be maintained, so that the material specific capacity is stabilized at 125 mAh / g. This also reminds us that although the conditions required for the first stage are more stringent, as long as the sintering of the second and third stages is well controlled, relatively stable oxygen-deficient materials can be obtained, which lays the foundation for the industrial large-scale preparation of the material and the product consistency is good.
[0138] It can be seen from Example 8 that the cooling rate in the second stage also has no significant effect on the oxygen defect formation effect of the product, the oxygen defect content is maintained at about 1%, and the specific capacity is 123-124 mAh / g.
[0139] From the comparison between Comparative Example 4 and Example 1, it can be seen that when there is no second stage hydrogen annealing and no third stage rapid cooling stage, oxygen defects will not be "generated" and "fixed" in the material.
[0140] From the comparison between Comparative Example 5 and Example 1, it can be seen that the method of forming oxygen defects by high-temperature sintering not only forms oxygen defects, but also destroys phosphate ions, thereby causing the collapse of the lattice structure and causing the material to lose the ability to deintercalate sodium ions. The calculated specific capacity is only 15 mAh / g.
[0141] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: S1. Press K 1-2x TiO 1-x The phosphorus source, potassium source, and titanium source are mixed in a stoichiometric ratio of PO4, and then mixed with a carbon source to obtain a slurry; wherein x = 0.001-0.1; S2, drying the slurry of S1 to obtain a precursor; S3, the precursor of S2 is treated in three stages to obtain a chemical formula of K 1-2x TiO 1-x PO4@C is a negative electrode material for sodium-ion batteries; The three-stage process includes: The first stage: heating to a first set temperature for heat treatment in an inert gas atmosphere; The second stage: the product of the first stage is cooled to 400-600°C in a hydrogen atmosphere for heat treatment; The third stage: the product of the second stage is cooled to the second set temperature at a rate of 10-20°C / min under a hydrogen atmosphere.
2. The sodium ion battery negative electrode material according to claim 1, characterized in that In step S1, at least one of the following features is included: (1) The potassium source includes one or more of potassium carbonate, potassium hydroxide, potassium sulfate and potassium dihydrogen phosphate; (2) The titanium source includes one or more of titanium dioxide, metatitanic acid, titanic acid and titanium tetrachloride; (3) The phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate and phosphorus pentoxide; (4) The carbon source includes one or more of graphite, activated carbon, hard carbon, graphene and carbon black.
3. The sodium ion battery negative electrode material according to claim 1, characterized in that In step S1, at least one of the following features is included: (1) In the sodium ion battery negative electrode material, the mass percentage of the carbon source is 1-5wt%; (2) The mixing method includes wet ball milling; (3) The mixing comprises the following steps: firstly mixing a phosphorus source, a potassium source and a titanium source to obtain slurry A, and then mixing slurry A with a carbon source to obtain slurry B; (4) The slurry contains a solvent; the solvent includes water or a mixed solvent of water and ethanol.
4. The sodium ion battery negative electrode material according to claim 1, characterized in that In step S2, the drying includes at least one of the following features: The drying method includes centrifugal spray drying; Preferably, the inlet air temperature of the centrifugal spray drying is 100-240°C; Preferably, the outlet air temperature of the centrifugal spray drying is 80-110°C; Preferably, the centrifugal speed of the centrifugal spray drying is 10000-20000 rpm.
5. The sodium ion battery negative electrode material according to claim 1, characterized in that In the first stage of step S3, at least one of the following features is included: (1) The inert gas includes argon and / or hydrogen; (2) The first set temperature is 600-800° C.; (3) The heating rate is 1-10°C / min; (4) The heat treatment time is 10-20 hours; (5) The flow rate of the inert gas is 5-15 L / min.
6. The negative electrode material for sodium ion battery according to claim 1, characterized in that: In the second stage of step S3, at least one of the following features is included: (1) The heat treatment time is 2-10 hours; (2) The cooling rate is 1-10°C / min; (3) The flow rate of the hydrogen is 10-20 L / min.
7. The negative electrode material for sodium ion battery according to claim 1, characterized in that: In the third stage of step S3, at least one of the following features is included: (1) The second set temperature is 20-30°C; (2) The flow rate of the hydrogen is 10-20 L / min; (3) The cooling method includes liquid cooling or air cooling.
8. A sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector and a negative electrode active layer arranged on at least one side of the current collector along the thickness direction, and the negative electrode active layer contains the sodium ion battery negative electrode material according to claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery contains the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Preparing method of positive electrode material of lithium batteries
CN106299354A
Synthesis and application of sodium ion battery electrode material KTiOPO4
CN108448095A
Preparation method of Ba0. 5Ti2 (PO4) 3 / C nanosphere negative electrode material
CN113562715A
NaTi2 (PO4) 3 (at) C micro-nano composite material as well as preparation method and application thereof
CN114873573A
Preparation method of sodium ion battery negative electrode material
CN116081591A